The emerging role of corporate information systems: An example from the area of business process-oriented learning - Dimitra Pappa; Lampros K. Stergioulas (International Journal of Business Science & Applied Management (IJBSAM), 2008)
Emerging business requirements, stemming from a holistic view over an organisation's activities, place additional pressure on technical infrastructures and call for operational agility and a better alignment between business and technology. Business process oriented learning unites corporate training and business process management. Given the importance of an organisation's human capital to business success, aligning individual training with business priorities, becomes a key challenge. The implementation of this new business service entails integrating learning into daily working tasks and putting in place mechanisms for the effective management of business processes, organisational roles, competencies and learning processes, to reduce the time to fill competency gaps and to build proficiency according to evolving business needs. In this paper we outline the main characteristics of this approach and provide insights regarding the changing role of the involved corporate information systems and the multiple aspects of the integration work.
Keywords: 650; information systems integration; service-oriented architectures